2019
DOI: 10.1002/prep.201800091
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Unsteady Combustion Model of AP/HTPB Propellant under Depressurization by Rotation

Abstract: In order to study micro‐scale combustion characteristics of base‐bleed propellant ammonium perchlorate/hydroxyl terminated polybutadiene (AP/HTPB) under rotation condition, a two‐dimensional unsteady rotating combustion model of periodic sandwich model of AP/HTPB was established. In the gas phase, a two‐step overall reaction was used to couple the gas‐solid boundary layer, the rotational momentum was fitted and the numerical simulation comparative analysis under the initial combustion pressure of 0.1 MPa–5 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The second is to use the level-set (LS) method, which relies on the evolution of a surrogate field, the isocontours of which are regarded as a sharp surface. This was originally applied by Wang et al [35] and others [36,37] to modeling surface regression in SCPs. Here, surface regression is effected by local calculation of regression rate, which is used to update the surrogate field at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The second is to use the level-set (LS) method, which relies on the evolution of a surrogate field, the isocontours of which are regarded as a sharp surface. This was originally applied by Wang et al [35] and others [36,37] to modeling surface regression in SCPs. Here, surface regression is effected by local calculation of regression rate, which is used to update the surrogate field at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion property of composite solid propellant is significantly affected by the mesoscopic structure of the burning surface [2, 3], which means that the burning rate at each point on the burning surface is different. However, the measured burning rate is usually an average value and not enough to characterize the propellant combustion property in detail.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the combustion efficiency obtained by a multi-location swirl injection gives a lower improvement with a 24 L/D motor (from 70 % to 76 %), but the improvement was significant with a 12 L/D motor with a single swirl injector (from 50 % to 74 %). Ye [10,11] established a two-dimensional periodic sandwich steady rotating combustion model of AP/HTPB, and the flame structure was simulated under the combustion pressure of 0.1-5.0 MPa and spinning speed of 0-10 800 rpm. He found that the deflecting angle of the gas flame is linearly positive with the pressure, and the trend of the average Reynolds number on the combustion surface is the same as the deflection angle of the gas flame.…”
Section: Introductionmentioning
confidence: 99%